1 2 2

:

  1. #1

    Jul 2012
    5,302

    :-
    1-
    = ^2 ( ^2 + 1 ) /
    :-
    = ^2 ( ^2 + 1 )^1/2
    = 1/2 ^2 ( ^2 + 1 )

    / = 1/2 [ ^2 2 / ^2 + 1 + ( ^2 + 1 ) 2 ]
    / = 1/2 [ 2 ^3 / ^2 + 1 + 2 ( ^2 + 1 ) ]
    = ^3 / ^2 + 1 + ( ^2 + 1 )

    2-
    = ( 2^ ( - 1 ) )
    /
    :-
    = 2^ + ( - 1 )^12
    = 2 + 1/2 ( - 1 )

    / = 2 + 1/2 ( - 1 )
    / = 2 + 1/ 2 - 2

    :-
    = ( ^2 - 1 )^
    ( ^2 - 1 ) = 2
    :-
    = ( ^2 - 1 )^

    = ( ^2 - 1 ) ^-1 2
    = 2 ( ^2 - 1 )^ - 1

    = 2 ( ^2 - 1 ) / ( ^2 - 1 )

    ( ^2 - 1 ) = 2 ( ^2 - 1 ) ^

    ) ^2 - 1 ) = 2

    :-
    = ^ , / = 1 / /
    :-
    = ^
    / = ^ - 1
    ^ = /
    = ) / )^ 1 /

    / = 1/ ) / )^ 1 / - 1 ( 1 / )
    / = 1 / ( / )^ 1/ - 1
    ^ = /
    / = 1 / ( / )^1 / - 1
    = 1 / ( ^ 1 - )
    = 1 / ^ - 1
    ^ - 1 = / / = 1 / /

    :-
    ( 1 - )^8
    :-
    ( 1 - )^8 , = 1 -
    = ^8
    / = 8 ^7 ................. / = - 1


    / = / / = 8 ^7 ( - 1 )
    = 8 ( 1 - )^7 - 1
    = - 8 ( 1 - )

    :-
    2 = /
    2 ( / ) + 2 ^2 2 = 1
    :-
    2 = ............
    ^2 2 2 + 2 / = 1

    2 ( / ) + 2 ^2 2 = 1

    :-
    = ^2 + 3
    = 2 + 1 , / = 12
    :-
    / = / = /
    = / = 2
    / = 2
    / = / / = 2 2 = 4
    = 4 ( 2 + 1 ) / = 12
    12 = 4 ( 2 + 1 )
    3 = 2 + 1 ................. = 1













  2. #2
      Eiman
    Jul 2011
    -
    14,750

    :

    .......

: 1 (0 1 )